English Phraseology in Teaching: Linguacultural Competency of Revealing the Semantic and Communicative Properties of Interjectional Phraseological Units - Makhkamova, Kamila; Atayeva, Gulbahor (International Journal of Psychosocial Rehabilitation, 2020)
In the present article we deal with the Interjectional phraseological units based on both dictionary materials and examples borrowed from fiction works.In the phraseological science the principle of studying phraseological units has been worked out. We follow the definition of a phraseological units given by A.V. Kunin who writes thata phraseological unit is “a fixed combination of words which fully or partially change their meanings” It means that a character, which is above the word level, stability and changed meanings of words in the combination are criteria of phraseological units together with other linguistic units, which define their special status in the language structure (Kunin, A.V., 2005).The object of our research make up substantive, verbal, adverbial, pronominal, numerical and the like phraseological units, we have taken only interjectional phraseological units, semantically analyzed them, classified them into groups according to their meanings.They are chosen and grouped as a special phraseological category called interjectional phraseological units which serve expressing various feelings, emotions and will inducements of the person. They are such units as By Love! Good Heavens! Draw it mild! Damn your eyes! By Jupiter! Etc. They express greeting, parting, wish admiration, gratitude, address appeals and other feelings. Below we stop on them in detail. Linguacultural Competency of students in revealing the Semantic and Communicative Properties of Interjectional Phraseological units.